Pengalaman Subjektif Individu dalam Hubungan Pacaran dengan Pasangan yang Mengalami Avoidant Personality Disorder: Studi Kualitatif - Nurjannah Nurjannah; Sri Nurhayati Selian (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to explore the subjective experiences of individuals in relationships with partners with Avoidant Personality Disorder (AvPD) tendencies through a qualitative approach. AvPD is characterized by a pattern of feelings of inadequacy, high sensitivity to rejection, and a tendency to avoid intense social interactions, including intimate relationships. The research method used a phenomenological design with in-depth interviews with three participants who had experience in romantic relationships with individuals with AvPD symptoms. Data were analyzed using thematic analysis techniques to identify emerging patterns of experience. The results showed that individuals in these relationships often experience complex emotional dynamics, such as confusion, frustration, and feelings of emotional unfulfillment. Participants expressed difficulties in building emotional closeness because their partners tended to maintain distance, avoid conflict, and have an excessive fear of rejection. On the other hand, participants also showed high empathy and attempted to understand their partners' psychological conditions, although this often resulted in emotional exhaustion. This study highlights the importance of psychological understanding, effective communication, and professional support in maintaining relationships with individuals with AvPD tendencies. These findings are expected to contribute to the development of psychological interventions and increase awareness of the dynamics of interpersonal relationships involving personality disorders.